Investigation of Disinfection Effect Using UV-C Ultraviolet Irradiation Robot - ANDO, Daisuke; HABU, Ryota; MORIYAMA, Norifumi; MEGUMI, Ryoya; YAMADA, Akiteru; RIKITAKE, Yuki; HIRABARA, Yasutoshi; NAKAYAMA, Yuki; KAWASAKI, Chiho; TAKAJO, Ichiro (Japanese Journal of Infection Prevention and Control, 2024)
The University of Miyazaki Hospital established UV-C ultraviolet irradiation robots to strengthen measures against nosocomial infections. In this study, we collected cultures and environmental samples from outpatient examinations and patient rooms before and after UV irradiation and compared the effects of UV-C irradiation time, irradiation distance, and object structure on the disinfection effect of the UV-C irradiation robot, as well as the disinfection effect of the UV-C irradiation robot on patient rooms following their use. As a result, a certain disinfection effect was confirmed by the UV-C irradiation. However, the disinfection effect may be insufficient because of factors such as inadequate irradiation distance, object structure, and the presence of dust. To achieve a higher level of disinfection, it is necessary to complement UV irradiation using a UV-C ultraviolet irradiation robot with regular cleaning practices. Special attention should be paid to areas where objects have complex structures, shadows are easily formed, and dust tends to accumulate. By combining UV irradiation with thorough cleaning of these specific areas, an enhanced disinfection effect can be anticipated.